What Happens with the Mind when the Brain Dies? - Gomez-Marin, Alex (Organisms. Journal of Biological Sciences, 2023)
A neuroscientist reflects on his near-death experience to ponder the nature of the human mind and the survival of consciousness after death. Ancient traditions, manifold personal experiences, nuanced philosophical views, and recent scientific evidence, all point to the brain as a filter (or receiver) of consciousness rather than its fanciful producer. No doubt, good-old-fashioned materialists —nowadays rebranded as physicalists, crypto-dualists, or illusionists wearing virtual reality goggles— insist that minds are “nothing but” what brains do. Nevertheless, a trans-materialist science can expand the scope and depth of the answers (and the questions) that really matter not only to science but also to human flourishing.